HUBUNGAN TINGKAT PENGETAHUAN TENTANG DISMENORE DENGAN SIKAP PENANGANAN DISMENORE PADA REMAJA PUTRI KELAS X DI SMAN 1 PETANAHAN - purwani, siti; -, herniyatun; yuniar, isma (LPPM STIKES MUHAMMADIYAH GOMBONG, 2010)
Dysmenorrhoea is the pain that occurs before and during 1-3 first day of menstruation period. The aim of this study is to find out the correlation between dysmenorrhoea knowledge level with dysmenorrhoea handling attitude of class x female students in Petanahan senior high school. The method from the research was non experimental design with cross-sectional approach. The number of Respondents were 67 class X senior high school female teenagers Data were analyzed by Kendal tau correlation test. Result of this study shows that there was 55 82.08% had less knowledge about dysmenorrhoea and handling attitude. Kendal tau correlation test showed significant value 0,021 with P < 0.05. It means that there was correlation between dysmenorrhoea knowledge level with dysmenorrhoea handling attitude. They need guide and looking for information about dysmenorrhoea by media electronic so their knowledge will be increase. Key words: Dysmenorrhoea, Knowledge, Attitude, Female students